Design Of Balanced Scorecard-Based Performance Measurement System For Small And Medium Enterprises: Case Study On Cv Erpa Utama Lombok, NTB - Whella Widhyasari Erpa; Saipul Arni Muhsyaf; Adithya Bayu S (International Journal of Business and Quality Research, 2023)
This study aims to design an objective strategy that is aligned with the Vision and Mission of CV. Erpa Utama and know the application of AHP and ANP methods in measuring the weight of each performance indicator in the perspective of the Balanced Scorecard that has been designed. This research is a case study using descriptive qualitative methods. Data was collected through questionnaires, interviews, and documentation. The informant in this study was the Director of CV. Erpa Utama. The results of this study analyze the weighting method of AHP and ANP to determine strategic priorities in managing company performance. AHP places Customer Perspective as a top priority, followed by Internal Business, Growth and Learning, and Finance. Meanwhile, ANP gives higher priority to Financial, Customer, Internal Business, and Growth and Learning Perspectives, reflecting a different approach to variable dependence. The prioritized KPIs are also different; AHP emphasizes Customer Satisfaction, Product Quality, and Customer Growth, while ANP highlights Product Innovation, Revenue Increase, and Customer Satisfaction. From a global perspective, AHP affirms priorities on Customer Satisfaction, Revenue Increases, and Employee Training, while ANP highlights Product Innovation, Revenue Increases, and Customer Satisfaction. Although both methods provide insight into resource allocation for operational efficiency, revenue growth, and customer satisfaction, differences in BSC (Financial Priority ANP, Customer Priority AHP) ratings show the influence of respondents' interpretation. Therefore, integration of weighting methods and regular evaluation is necessary to improve strategic decision making by understanding differences and accommodating changing organizational conditions.